National Athletic Trainers' Association position statement: Preparticipation physical examinations and disqualifying conditions - Conley, K. M.; Bolin, D. J.; Carek, P. C.; Konin, J. G.; Neal, T. L.; Violette, D. (Journal of Athletic Training, 2014)
Objective: To present athletic trainers with recommendations for the content and administration of the preparticipation physical examination (PPE) as well as considerations for determining safe participation in sports and identifying disqualifying conditions. Background: Preparticipation physical examinations have been used routinely for nearly 40 years. However, considerable debate exists as to their efficacy due to the lack of standardization in the process and the lack of conformity in the information that is gathered. With the continuing rise in sports participation at all levels and the growing number of reported cases of sudden death in organized athletics, the sports medicine community should consider adopting a standardized process for conducting the PPE to protect all parties. Recommendations: Recommendations are provided to equip the sports medicine community with the tools necessary to conduct the PPE as effectively and efficiently as possible using available scientific evidence and best practices. In addition, the recommendations will help clinicians identify those conditions that may threaten the health and safety of participants in organized sports, may require further evaluation and intervention, or may result in potential disqualification.